Bench-to-bedside review: Sepsis - from the redox point of view - Andrades, Michael Éverton (BioMed Central, 2011)
The pathogenesis of sepsis and its progression to multiple organ dysfunction syndrome and septic shock have been the subject of investigations for nearly half a century. Controversies still exist with regard to understanding the molecular pathophysiology of sepsis in relation to the complex roles played by reactive oxygen species, nitric oxide, complements and cytokines. In the present review we categorise the key turning points in sepsis development and outline the most probable sequence of events leading to cellular dysfunction and organ failure under septic conditions. We have applied an integrative approach in order to fuse current state-of-the-art knowledge about redox processes involving hydrogen peroxide, nitric oxide, superoxide, peroxynitrite and hydroxyl radical, which lead to mitochondrial respiratory dysfunction. Finally, from this point of view, the potential of redox therapy targeting sepsis is discussed.